Scintigraphic assessment of patellar vascularity in total knee replacement surgeries following lateral release - Padma Subramanyam (Thieme Medical and Scientific Publishers Pvt. Ltd., 2012)
For a total knee replacement (TKR) to function well, the patella must track centrally in the trochlear groove. Lateral retinacular release (LR) is performed as an integral step in TKR to avoid maltracking. Patellar resurfacing and infra patellar fat pad excision are other small surgical procedures performed during TKR that can also easily deprive the patella of its vascularity. A three phase bone scan helps in the assessment of patellar vascularity. Literature review reveals a variable association (10-56%) of LR and patellar hypovascularity in Caucasians. Objective: LR release done in TKR is known to compromise patellar viability, while its extent and severity is still debated. Our prospective study was undertaken to evaluate the effects of LR on patella along with other variables like patellar resurfacement, fat pad excision, patelloplasty on knees by 99m Technetium labeled methylene diphosphonate ( 99m Tc MDP) three phase bone scintigraphy (TBS). Materials and Methods: 45 TKRs were done between Jan 05 and Jan 06. Of them, 15 patients (21 knees) of primary TKR were considered prospectively. Patients undergoing uni/bilateral TKR due to symptomatic knee osteoarthritis were only selected for this study. Pre- and immediate postoperative TBS was done with modified positioning of knee joints (adducted, externally rotated and flexed to 30°) to visualize patellae away from knee joint, which otherwise gets superimposed on the femoral condyles. A follow-up TBS at 8-10 weeks was done in patients showing immediate post-op patellar hypovascularity. Results: 12/21 knees (57%) needed LR. Of these 12 knees, 8 (66%) showed hypovascularity; whereas 9 knees with no LR, 1 knee showed hypovascularity. All 9 knees (8 post LR+1 without LR) with hypovascularity underwent TBS again at 8-10 weeks and were found to show improvement in their vascularity status in all cases. Conclusion: Our study showed a higher incidence of LR in our population (57%). Association of LR and patellar ischemia was significant, about 16 times the risk. MDP bone scintigraphy is the only objective tool to quantify patellar vascularity. Overall 42.8% knees post-TKR had a transient patellar ischemia, and 38% of them were following LR. All of them recovered at 8-10 weeks postoperatively.